Isu Megapolitan Jabodetabekjur Dalam Konteks Pengelolaan Pembangunan dan Revisi UU No. 34/1999 - Denny Zulkaidi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
Jabodetabekjur Megapolitan issue which was launched at the same time with the revision of Law No. 34/1999 concerning The Government of DKI (Daerah Khusus Ibukota, Special District Region) Jakarta has raised pros and cons from different parties. Regencies and municipalities next to the DKI Jakarta immediately support this concept, while the Province of West Java and the Province of Banten respond differently against the concept. The emergence of pro and con, and inappropriate perception and responds toward this concept mainly come from lack of understanding of the concept, undeliverable the content of megapolitan concept completely, and lack of communication between the Province of DKI Jakarta and related provincial and regency/municipal authorities. The issue can be discussed from three different views. First, as rapidly developed urban areas growing into a large continuous urban area, the Jabodetabekjur region requires the megapolitan management concept to manage development within a large scale urban area. Second, as the implementation of